Solutions and Strategies to Reduce Damaging Impact of Single-Use Plastic Bag in Toledo City - Genon, Jamaica; Mabunay, Jessa; Opsima, James; Zamora, Rochelle; Repaso, Jay; Sasan, John Michael Villagorda (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
The goal of this study is to gain a better understanding of residents' personal concerns about improper plastic disposal and to give voice to their thoughts about the Toledo City Government's prospective ideas and approaches for minimizing the city's plastic pollution. Residents of Magdugo, Toledo City, Cebu, Philippines, have been subjected to increasing levels of plastic pollution. The vast number of discarded plastic items that eventually end up in canals, drainage systems, and city streets, generating flooding that poses a severe challenge in agriculture, health, and sanitation. According to the findings, the city's inefficient waste management system has resulted in a massive accumulation of durable plastics. Toledo City, on the other hand, has improved waste management, restored cleanliness, and minimized the environmental effect of plastics through regulatory initiatives. The majority of citizens in Toledo City have enthusiastically embraced the city's ordinance prohibiting the use of plastic bags. Plastic bag littering has been shown to decrease throughout the city, resulting in a cleaner and healthier environment. The city's achievement might serve as a model for other places that have yet to abolish plastic bags. As a result of a cleaner and healthier environment, people have become more productive, and tourists have returned to the city, contributing to the city's economic growth. Policy management in the reduction of plastic pollution.